Removal of Diethylene Glycol from Wastewater by Photo Aeration - Alsayer, Ibrahim A. (Engineering, Technology & Applied Science Research, 2024)
Photo air oxidation combines the use of ultraviolet (UV) light and air as an oxidant to degrade diethylene glycol (DEG) in wastewater. DEG is well known for its high chemical oxygen demand and has raised some serious environmental issues, since the conventional biological treatment package in plants may not be able to treat the waste in an effective manner. UV light generates highly reactive species, such as hydroxyl radicals (•OH), which can react with DEG and break it down into smaller, less harmful compounds. Air, specifically oxygen (O2), can act as an additional oxidant in the process, assisting in the degradation of DEG. The UV light source, such as low-pressure mercury lamps that emit at around 254 nm, is still needed to initiate the generation of hydroxyl radicals. The presence of oxygen in wastewater allows the hydroxyl radicals to react with DEG more effectively, improving the oxidation process. In the present research work, the effect of airflow rate, UV light intensities, oxygen partial pressure, and initial DEG concentration on photo-oxidation of DEG in wastewater was examined. We have also performed a kinetic study, from which the reaction order and the rate constant were determined.